2020
DOI: 10.1038/s41598-020-63992-8
|View full text |Cite
|
Sign up to set email alerts
|

Bmi1 inhibitor PTC-209 promotes Chemically-induced Direct Cardiac Reprogramming of cardiac fibroblasts into cardiomyocytes

Abstract: The development of therapeutic approaches based on direct cardiac reprogramming of fibroblasts into induced-cardiomyocytes (iCM) has emerged as an attractive strategy to repair the injured myocardium. The identification of the mechanisms driving lineage conversion represents a crucial step toward the development of new and more efficient regenerative strategies. To this aim, here we show that pretreatment with the Bmi1 inhibitor PTC-209 is sufficient to increase the efficiency of Chemical-induced Direct Cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Clusters of ChIP-Seq read alignments were identified employing MACS software (version 1.3.7.1). For ChIP-qPCR, samples were prepared as previously described ( 41 ). Supernatant obtained without antibody was used as an input control.…”
Section: Methodsmentioning
confidence: 99%
“…Clusters of ChIP-Seq read alignments were identified employing MACS software (version 1.3.7.1). For ChIP-qPCR, samples were prepared as previously described ( 41 ). Supernatant obtained without antibody was used as an input control.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, pharmacological or genetic inhibition of EGFR signaling increased AGHMT-mediated reprogramming efficiencies in MEFs, adult CFs, and adult TTFs (Hashimoto et al, 2019 ). EGFR signaling also results in the activation of pro-inflammatory signaling via activation of the JAK-STAT pathway, which is known to impair the reprogramming process (Efe et al, 2011 ; Jayawardena et al, 2012 ; Testa et al, 2020 ). Pharmacological inhibition of JAK2 enhanced reprogramming efficiency, similar to EGFR inhibition (Hashimoto et al, 2019 ).…”
Section: Strategies For Cardiac Repairmentioning
confidence: 99%
“…Knockdown of polycomb repressive complex 1 component Bmi1 facilitated removal of the transcriptionally repressive mark Histone H2A Lysine 119 ubiquitination (H2AK119ub) at cardiac genes and corresponded to increased H3K4me3 levels, increased expression, and increased reprogramming efficiency by polycistronic M-G-T (Zhou et al, 2016 ). Furthermore, 24 h pretreatment of MEFs or CFs with the Bmi1 inhibitor PTC-209 repressed STAT3-, IL-6-, and ERK1/2-mediated inflammatory signaling and resulted in a ~25% increase in the number of αMHC-GFP positive cells generated by the CRFVPT small molecule combination (Testa et al, 2020 ). Targeted depletion of additional epigenetic regulators including lysine-specific methyltransferases Kmt2a, Kmt2b , and Kmt2e via shRNA delivery impaired the reprogramming process whereas depletion of chromatin remodeler complex and cohesion complex subunits Ruvbl1/Bcor and Stag2 , respectively, enhanced reprogramming by polycistronic M-G-T (Zhou et al, 2018 ).…”
Section: Strategies For Cardiac Repairmentioning
confidence: 99%
“…Direct cardiac reprogramming generates cardiomyocytes from fibroblasts without passing through a stem cell state [ 109 ]. This transdifferentiation requires a massive epigenetic remodeling to allow the silencing of fibroblast gene programs and, in parallel, the upregulation of the transcriptional rate of genes in cardiogenic loci [ 110 ]. Very recently, it has been demonstrated that the use of soft matrices resembling the native myocardium improved cardiac reprogramming by suppressing YAP/TAZ signaling [ 111 ].…”
Section: Yap and Taz In Tissue Regeneration And Cell Reprogrammingmentioning
confidence: 99%